The general pattern of Islamic thought in the Qur'an / by Sayyed Ali Khamenei ; translated by Alireza Anoushiravani - Khamenei, Ali
En el verso de la portada: Islamic Propagation OrganizationTextos del Corán en escritura árabe y su transcripción al ingles